(3CKQ GdOYhi GdLfGFjI Ydi GdOYhi GdJCOjHjI (B/ s - (3Ydi Mdei eUWai WdHs; (3YeQ eMeO eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JYO GdeNGdaI GdJCOjHjI GdCSGS GdPi JOhQ Mhdg cd OQGSI eJYdbI HGdJCOjH(B: (3h Jbhe cd ef GdLQjeI GdLfGFjI h GdeNGdaI GdJCOjHjI Ydi acQI GdNWC HeYfi Cf GdhGbYI GdefShHI Edi GdehXa ShGA cGfJ JTcd LQjeI LfGFjI(B: (3Ch eNGdaI JCOjHjI JHfj Ydi Cfg CJi CaYGdkG(B: (3Ch GeJfY Yf GdbjGe HCYeGd JeKd GfMQGakG Yf GdSdhc Gdbhje GdPi jJWdHg GdeLJeY(B: (3Ch GdhXjaI GdYGeI GdJj jbhe HCYHGFgG(B. (3h ef GdLOjQ HGdPcQ Cf GdLQGFe GdLfGFjI(B: (3h GdLQGFe GdJCOjHjI JfJejGf Edj CUd hGMO h gh GdLQGFe GdYbGHjI(B: (3h geG h Ef cGfG ef CUd hGMO(B: (3EdG EfgeG efaUdGf dGNJdGa WHjYI cd efgeG(B: (3h eY Pdc aEf GdLQjeI GdLfGFjI JMOK BKGQgG Ydj GdLQjeI GdJCOjHjI(B: (3h Ydj eQJcHjgG MGd chfg NGVYkG ddfXGe GdJCOjHjs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B313-344s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdOYhi GdJCOjHjIs; (3GdOYhi GdLfGFjIs; (3GdehXa GdYGes; (3GdJMbjb GdEOGQjs; (3GdeMceI GdJCOjHjIs; (3GdYdGbI Hjf GdLQjeI GdJCOjHjI hGdLQjeI GdLfGFjIs; (3CQcGf GdLQjeI GdJCOjHjIs; (3CQcGf GdLQjfI GdLfGFjIs; (3CKQ GdJMbjb GdLfGFj Ydi GdJMbjb GdJCOjHj s; (3GNJUGU GdfjGHI GdEOGQjI HGdJMbjbs; (3SdWI GdLgGR GdeQcRj ddeMGSHGJ aj GdEMGdI Edi GdeMGceI GdJCOjHjI s; (3SdWGJ GdJCOjHs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs